ON THE CONJUGATION INVARIANT PROBLEM IN THE MOD p DUAL STEENROD ALGEBRA - Turgay, Ne¸set Deniz (Italian Journal of Pure and Applied Mathematics, 2015)
The Leibniz–Hopf algebra \(\mathcal{F}\) is the free associative Z-algebra on one generator in each positive degree, with coproduct given by the Cartan formula. Fix an odd prime p, and let \(\mathcal{A}\) denote the Bockstein–free part of the mod p Steenrod algebra. We investigate an alternative approach to the conjugation invariant problem in the dual Steenrod algebra \(\mathcal{A}\)* using the conjugation invariants in \(\mathcal{F}\)* ⊗ Z/p.